Co-operatives in agricultural and rural development in kerala: a review - Carmel Thomas AND Joseph James
A substantial sector of the economy had to rely on unorganized money market for meeting its requirements of credit .Though agriculture has always been the most important sector in the country’s economy, it received little credit from commercial and co-operative Banks. Commercial banks being urban oriented, catered primarily to the needs of mostly vagaries of weather and this discouraged the commercial banks from entering the field of agricultural credit. The responsibility for providing credit to agriculture should be that of co-operatives and that co- operatives should be strengthened for that purpose.